Integrating Disaster Risk Reduction into Science Education to Strengthen Higher Education Resilience: Evidence from A Philippine HEI - Biscocho, Sheryl; Punzalan, Christopher; Lo, Noble (Jurnal Pendidikan IPA Indonesia, 2026)
Natural disasters continue to pose great global challenges, intensified by urbanization and increasing human vulnerability. These risks expose higher education institutions (HEIs) to greater disaster impacts, highlighting the need for effective disaster risk reduction (DRR) systems and educational approaches that cultivate resilience. This study assessed DRR compliance at a Philippine HEI while examining the extent to which science education supports disaster resilience and sustainable development initiatives. Using a convergent mixed-method design, quantitative survey data collected from 99 students and 87 faculty members (Total number of respondents is 186) and qualitative focus group discussions (8 group members per group with 8 teams of 64 participants,) were collected and analyzed across four DRR domains: Prevention and Mitigation, Preparedness, Response, and Rehabilitation and Recovery. Findings revealed a moderate level of overall DRR compliance (Overall Mean = 3.41, SD = 0.78 on a 5-point Likert scale), indicating that DRR measures were generally implemented but remained inconsistent across domains. Disaster Response emerged as the strongest domain. (Mean = 4.12, SD = 0.65), reflecting well-established emergency procedures and response mechanisms. In contrast, lower scores were recorded in Preparedness (Mean = 3.08, SD = 0.82), Prevention and Mitigation (Mean = 3.25, SD = 0.79), and Rehabilitation and Recovery (Mean = 3.19, SD = 0.85). Moreover, significant gaps were identified in preparedness planning, infrastructure adequacy, psychosocial support, and the systematic integration of DRR concepts into science and general education curricula. Qualitative findings further showed that science education initiatives on disaster awareness and resilience were often,neglected and poorly aligned with institutional DRR policies and practices. These results suggest that while operational response systems have developed in its own way, long-term institutional resilience requires stronger preparedness mechanisms and a more deliberate curricular integration of DRR competencies. By examining the alignment between institutional DRR compliance and science education practices in higher education, this study provides empirical evidence on how educational and organizational systems can be integrated to strengthen disaster resilience and support the achievement of the Sustainable Development Goals.